2012
DOI: 10.5194/hessd-9-4161-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional effects of vegetation restoration on water yield across the Loess Plateau, China

Abstract: The general relationships between vegetation and water yield under different climatic regimes are well established at a small watershed scale in the past century. However, applying the basic theories to evaluate the regional effects of land cover change on water resources has been rarely done due to the complex interactions of vegetation and climatic variability and hydrologic processes at the large scale. The objective of this study was to explore ways to examine the spatial and temporal effects of a l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…From the perspective of the water balance equation TWSC = P − ET − R , the relative contributions of P , ET , and R to the spatial changes in TWSC were investigated from 2003–2010 using monthly data due to data availability. The P ‐ ET value, which has been regarded as the water yield (Feng et al, ), was investigated in this study. Before computing the linear trends and relative contributions, the annual cycle was removed from each water budget component.…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of the water balance equation TWSC = P − ET − R , the relative contributions of P , ET , and R to the spatial changes in TWSC were investigated from 2003–2010 using monthly data due to data availability. The P ‐ ET value, which has been regarded as the water yield (Feng et al, ), was investigated in this study. Before computing the linear trends and relative contributions, the annual cycle was removed from each water budget component.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the launching of the GFG project, the arable land area sharply decreased to 1349.07 km 2 in 2008. Undoubtedly, the GFG project contributed largely to reductions in runoff and sediment production on the sloping terrain (Zhang et al ., ; Rustomji et al ., ; Feng et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It was generally accepted that soil and water conservation measures played major roles in the reductions of runoff and especially sediment load in the watersheds in the Loess Plateau (Rustomji et al ., ; Feng et al ., ; Gao et al ., ). Rustomji et al .…”
Section: Discussionmentioning
confidence: 99%
“…() applied a modelling approach to a catchment in the region and found that climate variability contributed to 95% of the streamflow reduction while land use changes generated limited impact. More recently, a number of studies examined the trends in streamflow and sediment load in response to land use change in the Loess Plateau (Gao et al ., ) and how vegetation restoration affected catchment water yield because of implementation of the Grain‐for‐Green Program (Feng et al ., ). Liang et al .…”
Section: Introductionmentioning
confidence: 99%